Effect of the Plasma Gas Type on the Surface Characteristics of 3Y‐TZP Ceramic - Kang, Sung Un; Kim, Chul Ho; Kim, Hee Kyung; Yoon, Ye Won; Kim, Yu Kwon; Kim, Seung Joo (International Journal of Molecular Sciences, 2022)
Plasma surface treatment can be an attractive strategy for modifying the chemically inert nature of zirconia to improve its clinical performance. This study aimed to clarify the effect of plasma gas compositions on the physicochemical surface modifications of 3 mol% yttria‐stabilized zirconia (3Y‐TZP). The cold, atmospheric plasma discharges were carried out by using four different plasma gases, which are He/O2, N2/Ar, N2, and Ar from an application distance of 10 mm for 60 s. Static contact angles were measured to define the surface free energy. Changes in elemental compo-sition, surface crystallinity, and surface topography were assessed with X‐ray photoelectron spectroscopy (XPS), X‐ray diffraction (XRD), confocal laser scanning microscopy (CLSM), and scanning electron microscopy (SEM), respectively. A significant decrease in water contact angle was observed in all plasma groups with the lowest value of 69° in the N2/Ar group. CLSM and SEM investigations exhibited no morphological changes in all plasma groups. XPS revealed that a reduction in the surface C content along with an increase in O content was pronounced in the case of N2/Ar compared to others, which was responsible for high hydrophilicity of the surface. XRD showed that the changes in crystallite size and microstrain due to oxygen atom displacements were observed in the N2/Ar group. The N2/Ar plasma treatment may contribute to enhancing the bioactivity as well as the bonding performance of 3Y‐TZP by controlling the plasma‐generated nitrogen functionalities.
Keywords: Ceramics; Materials Testing; Microscopy, Electron, Scanning; Plasma Gases; Surface Properties; X-Ray Diffraction; Yttrium; Zirconium; Nitrogen; Plasma gases; Surface properties; Wettability; Zirconium oxide